Analysis of Cost Factors and Family Motivation on Adherence to Follow-up Treatment for Patients After Cardiac Catheterization at NTB Provincial Hospital - Heri Herdiansyah Akbar; Saimi; M. Karjono (Jurnal Penelitian Pendidikan IPA, 2026)
Cardiovascular disease represents a global mortality burden with suboptimal medication adherence (40-60%) after cardiac catheterization, resulting in increased complications and rehospitalization. This study aims to analyze the cost determinants and family motivation for medication adherence among patients after coronary intervention at the NTB Provincial General Hospital. This cross-sectional study involved 85 respondents using purposive sampling, with the Morisky Medication Adherence Scale, Family Support Scale, and a validated cost questionnaire as instruments. Chi-Square analysis was applied to test the association of variables with a significance level of 0.05. The results showed that the majority of respondents had high financial capacity (64.7%), substantive family motivation (62.4%), and superior adherence (64.7%). Economic capacity had a significant effect on adherence (p<0.001), with patients with high capacity showing 87.3% adherence versus 23.3% in the moderate group. Optimal family motivation resulted in 84.9% adherence compared to 31.3% in the moderate support group (p<0.001). The study concluded that financial accessibility and familial support are crucial predictors of treatment adherence, indicating the urgency of implementing inclusive financing schemes and structured family education programs to optimize long-term cardiovascular outcomes.